Effect of Water Quality on Efficiency of Holding Solutions for Cut Roses - Lop Phavaphutanon; Saichol Ketsa (Agriculture and Natural Resources, 1990)
The effect of water quality on efficiency of holding solutions for ‘Christian Dior’ cut roses was studied in relation to vase life, blueing, bent neck, water consumption, water uptake and fresh weight changes. The results showed that holding solutions containing 200 ppm sodium benzoate + 5% sucrose and chrysal® with tap water was less efficient than those with deionized water, whereas the efficiency of holding solution containing 100 ppm Physan -20+ 5 % sucrose was not affected by water quality.